THE INFLUENCE OF Acanthus ilicifolius EXTRACTS TO HISTOPATHOLOGICAL ON HEPATOPANCREAS OF TIGER SHRIMP (Penaeus monodon F.) - G. Saptiani; S. B. Prayitno; S. Anggoro; C. A. Pebrianto (International Journal of Marine and Aquatic Resource Conservation and Co-existence, 2017)
ABSTRACTAssesing the influence of the leaf extract to histopathological on hepatopancreas of shrimp as protection from Vibrio harveyi. Crude, ethyil acetate, and n-butanol fraction was given by dipping method. The best survival was the fraction of n-butanol 300 ppm, followed by n-butanol 200 ppm and 700 ppm etyl acetate fraction. It reduced the prevalence of attacks and improved the survival of shrimp. The best pathophysiological and pathological anatomy of shrimp was n-buthanol fraction, followed etyl acetat fraction and then crude. Histopathological of hepatopancreas was normal on n-butanol fraction, normal and minor in damage on etyl acetat fraction and crude, and minor to moderate damage on antibiotic Key words: Acanthus ilicifolius, Vibrio harveyi, histopathological, hepatopancreas